Obesity and people with disabilities: The implications for health care expenditures. (5th September 2013) - Anderson, Wayne L.; Wiener, Joshua M.; Khatutsky, Galina; Armour, Brian S.
<x xml:space="preserve">Abstract</x> Objective This study estimates additional average health care expenditures for overweight and obesity for adults with disabilities vs. without. Design and Methods Descriptive and multivariate methods were used to estimate additional health expenditures by service type, age group, and payer using 2004–2007 Medical Expenditure Panel Survey data. Results In 2007, 37% of community‐dwelling Americans with disabilities were obese vs. 27% of the total population. People with disabilities had almost three times (2, 459) the additional average obesity cost of people without disabilities (889). Prescription drug expenditures for obese people with disabilities were three times as high and outpatient expenditures were 74% higher. People with disabilities in the 45‐ to 64‐year age group had the highest obesity expenditures. Medicare had the highest additional average obesity expenditures among payers. Among people with prescription drug expenditures, obese people with disabilities had nine times the prevalence of diabetes as normal weight people with disabilities. Overweight people with and without disabilities had lower expenditures than normal‐weight people with and without disabilities. Conclusions Obesity results in substantial additional health care expenditures for people with disabilities. These additional expenditures pose a serious current and future problem, given the potential for higher obesity prevalence in the coming decade.